Analisis dan Perancangan Sistem Personalisasi dan Identifikasi Absensi Dosen Berbasis Smartcard Mifare Menggunakan Java Card Applet - Nofita Rismawati; Muhamad Femy Mulya (Jurnal SISKOM-KB (Sistem Komputer dan Kecerdasan Buatan), 2019)
Smartcard is an invention in the field of IT that has simplified human life because it has many functions and capabilities to store data. The advantages of a smartcard are rewritable data, extensive data capacity, support for reading multiple data carriers (support for multiple tag reads), robust physicality and smart task. The purpose of this study is to analyze and design a system of personalization and identification for the attendance of lecturers by utilizing Mifare's smartcard technology using a java card applet that can facilitate the lecture attendance process on a campus. Besides that, it also helps interested parties (in this case, campus management) in evaluating the performance of a lecturer. This study uses the Prototype / Prototyping model research method with the Unified Modeling Language (UML) approach. The results of this study are a prototype design personalization system and identification of lecturer attendance based on Mifare smartcard technology using java card applets, as well as the results of testing the accuracy of prototype readings from the Mifare smartcard personalization and identification system with smartcard readers using Java card applets.